Valorization of broccoli by-products: seasonal variations in bioactive compounds and their biostimulant effects on pak choi germination - Lorena Albaladejo-Marico; Maria Gomez-Molina; Paula Garcia-Ibañez; Micaela Carvajal; Lucia Yepes-Molina (PLoS ONE, 2025)
The use of plant-based biostimulants is a sustainable strategy to enhance crop growth while mitigating the environmental impact of synthetic agrochemicals. Broccoli by-products, rich in bioactive compounds, have emerged as a promising resource, though their composition is influenced by plant growing conditions. This study investigates the biostimulant potential of broccoli-derived extracts obtained from leaves, stems, and petioles of plants cultivated in three different seasons (autumn, winter, and spring) and their effect on the germination and early growth of pak choi (Brassica rapa subs. chinensis L.) seeds. A comprehensive biochemical characterization, including mineral content, glucosinolates, and phenolic compounds, was conducted to explore how seasonal and tissue-specific variations impact their composition and biostimulant efficacy. Principal Component Analysis (PCA) revealed distinct metabolic profiles across seasons and plant tissues, with leaf-derived extracts showing higher correlations with phenolic acids and trace minerals, whereas petiole and stem extracts were associated with macronutrients. Germination assays demonstrated that extracts from autumn and winter exhibited the highest biostimulant activity, likely due to their enriched secondary metabolite profiles and well-balanced mineral composition. In contrast, spring extracts, despite their higher macronutrient content, showed limited biostimulant effects, possibly due to physiological constraints in broccoli plants during spring, when they experience reduced bioactive potential. PCA and correlation analysis identified metabolites, particularly sinapic acid and glucobrassicin, as key contributors to enhanced seedling development. Furthermore, a positive relationship between sulfur content and glucosinolate levels suggests that sulfur concentration could serve as a useful quality marker for assessing the bioactivity of broccoli-based biostimulants. This study underscores the potential of broccoli-derived extracts as sustainable biostimulants for improving germination and seedling development in pak choi. The findings highlight the influence of seasons on the bioactive composition of extracts, with low temperatures and high relative humidity favoring the accumulation of secondary metabolites and an optimal nutrient balance in plants.